Thursday

August 28, 2014

August 28, 2014

Posted by **Karlee** on Sunday, April 21, 2013 at 1:14pm.

(a) f(-4)=

(b) f(-x)=

(c) -f(x)=

(d) f(x+h)=

- For the function defined by...HELP -
**Steve**, Sunday, April 21, 2013 at 5:37pmjust plug and chug:

f(-4) = 3(16)+5(-4)+2 = 30

f(-x) = 3(-x)^2+5(-x)+2 = 3x^2-5x+2

-f(x) = -(3x^2+5x+2) = -3x^2-5x-2

f(x+h) = 3(x+h)^2+5(x+h)+2

= 3x^2+6hx+3h^2 + 5x+5h + 2

= 3x^2 + (6h+5)x + (3h^2+5h+2)

**Related Questions**

Calculus - A cubic polynomial function f is defined by f(x) = 4x^3 + ax^2 + bx...

Calculus - A cubic polynomial function f is defined by f(x) = 4x^3 + ax^2 + bx...

math grade 11 - A quadratic function is defined by f(x)= 3x^2+4x-2. A linear ...

math grade 11 - A quadratic function is defined by f(x)= 3x^2+4x-2. A linear ...

domain - Find the domains of f and f' 1, f(x) = xe^x 2. f(x) = x^(3/5) 3. f(x...

Let f be the function be defined by f(x)=5^((2x^2) - Let f be the function be ...

Algebra - Can you please help me with the following problems? Find the ...

Maths - Correct each of the following incorrect statements: 1)The inverse of the...

pre-calculus - for the function f defined by: (x)=3x^2+3x+2;find the following ...

Calculus - Functions? - #1. A cubic polynomial function f is defined by f(x) = ...